Species richness, habitable volume, and species densities in freshwater, the sea, and on land - Michael N Dawson (Frontiers of Biogeography)
Approximately 0.5–2.0 million eukaryotic species inhabit the seas, whereas 2.0–10.0 million inhabit freshwater or the land. Much has been made of this several-fold difference in species richness but there is little consensus about the causes. Here, I ask a related question: what is the relative density of species in marine and non-marine realms? I use recent estimates of global eukaryotic species richness and published estimates of the areal coverage and depth of habitat for freshwater, marine, and terrestrial biomes. I find that the marine realm harbors ~99.83% of the habitable volume on this planet. Eukaryotic species density of the marine realm is ~3600-fold (i.e., 3-4 orders of magnitude) less than that of non-marine environments. Species–volume relationships (SVRs) help reconcile actinopterygian fish diversity with global primary productivity and emphasize the interacting roles of abiotic and biotic complexity in shaping patterns of biodiversity in freshwater, the sea, and on land. Comparing SVRs of habitats within and across realms may help resolve the factors and interactions that influence species density.